2001
DOI: 10.1080/14616730110056946
|View full text |Cite
|
Sign up to set email alerts
|

The coherence of dyadic behavior across parent–child and romantic relationships as mediated by the internalized representation of experience

Abstract: Attachment theory suggests, first, that patterns of dyadic behavior cohere across salient relationships and, second, that such linkages are mediated by working models, defined as cognitive/emotional representations of relationships abstracted from dyadic experience. In this longitudinal study, adolescents' (age 19) Adult Attachment Interview (AAI) coherence ratings and classifications (e.g. working model proxies) were related prospectively to their observed dyadic behaviors with romantic partners in young adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 16 publications
(29 reference statements)
1
31
0
Order By: Relevance
“…Although previous research has suggested that adolescents' attachment security with parents may guide their expectations for romantic relationships over time (e.g., Roisman et al, 2001), this research does not speak to the mechanisms by which insecurity may be related to particular maladaptive romantic schemas or behaviors. Furthermore, findings from attachment research often fall prey to the criticism that "all good things go together," because they do not identify the conditions under which specific aspects of attachment security are associated with different outcomes (Waters and Dean, 1985).…”
Section: Discussionmentioning
confidence: 85%
“…Although previous research has suggested that adolescents' attachment security with parents may guide their expectations for romantic relationships over time (e.g., Roisman et al, 2001), this research does not speak to the mechanisms by which insecurity may be related to particular maladaptive romantic schemas or behaviors. Furthermore, findings from attachment research often fall prey to the criticism that "all good things go together," because they do not identify the conditions under which specific aspects of attachment security are associated with different outcomes (Waters and Dean, 1985).…”
Section: Discussionmentioning
confidence: 85%
“…One recent study also found security of attachment to be linked to high levels of maternal sensitivity, as measured by how well mothers were able to predict the ways that their teens would respond to a questionnaire about their own competence (Allen et al, 2003 ). Secure states of mind are also associated with warmer, more accepting, open, and engaged interactions with parents as observed from interactions and as reported by adolescents (Becker -Stoll, Delius, & Scheitenberger, 2001 ;Ducharme, Doyle, & Markiewicz, 2002 ;Roisman, Madsen, Hennighausen, Sroufe, & Collins, 2001 ).…”
Section: Attachment Security and The Push For Autonomymentioning
confidence: 95%
“…Interestingly, research also suggests that younger teens with self -reported secure attachment styles report turning to romantic partners less often than mothers to fulfill attachment functions, which the authors consider to be a developmentally appropriate pattern for this age group (Markiewicz et al, 2006 ). In late adolescence, secure states of mind have also been linked to the subsequent quality of interactions with a romantic partner; such interactions are characterized by willingness to express ideas, ability to resolve conflict, and mutual caring and pleasure in the other person (Roisman et al, 2001 ;. Further, research with young adults indicates that security of attachment is linked to healthier sexual behavior: Securely attached young women are more likely to require some emotional commitment from partners before engaging in sex and are also likely to have somewhat less permissive attitudes toward sexuality (Januszewski, Turner, Guerin, & Flack, 1996 ).…”
Section: Attachment and Adolescent Social Functioningmentioning
confidence: 99%
“…For example, Bouthillier et al (2002) used the AAI to assess "state of mind with respect to attachment" (Main et al, 1985) to mother and found that individuals who were categorized by the AAI as insecure were more likely to use destructive tactics during a conflictual interaction with a romantic partner. In addition, individuals categorized as insecure in the AAI exhibited more negative emotion during conflictual interactions (i.e., more expressions of contempt, withdrawal, and stonewalling) and less positive emotion (e.g., Babcock et al, 2000;Creasey & Ladd, 2005;Roisman et al, 2005;Roisman et al, 2001). Because attachment security as assessed by the AAI likely derives to a significant degree from the quality of the parent-child relationship in terms of behavioral interactions, these findings offer indirect support for the proposition that this relationship will affect the behavioral quality of later romantic unions.…”
Section: Parent-child Interactions and Later Romantic Interactionsmentioning
confidence: 99%